2018
DOI: 10.3390/molecules23071643
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hydrophilicity and Inducing Bone-Like Apatite Formation on PPBES by Polydopamine Coating for Biomedical Application

Abstract: Copoly(phthalazinone biphenyl ether sulfone) (PPBES) as a commercially available polyarylether is a promising orthopaedic implant material because its mechanical properties are similar to bone. However, the bioinert surface of polyarylether causes some clinical problems after implantation, which limits its application as an implant material. In this study, the surface of PPBES was modified by a biomineralization method of polydopamine-assisted hydroxyapatite formation (pHAF) to enhance its cytocompatibility. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The modified PPBES demonstrated low cytotoxicity (almost negligible) to NIH-3T3 cell lines, while cell adhesion was increased by 1.2-fold as detected by scanning electron microscopy. The results open a new approach for surface modification of poly(aryl ether) derivatives to extend their application in bone tissue engineering [ 68 ]. The pHAF was also applied in a PCL scaffold to obtain highly osteoinductive implantation composite (PCL-PDA-HA).…”
Section: Application Of Pda-ha Functionalization For Implant Matermentioning
confidence: 99%
“…The modified PPBES demonstrated low cytotoxicity (almost negligible) to NIH-3T3 cell lines, while cell adhesion was increased by 1.2-fold as detected by scanning electron microscopy. The results open a new approach for surface modification of poly(aryl ether) derivatives to extend their application in bone tissue engineering [ 68 ]. The pHAF was also applied in a PCL scaffold to obtain highly osteoinductive implantation composite (PCL-PDA-HA).…”
Section: Application Of Pda-ha Functionalization For Implant Matermentioning
confidence: 99%
“…For instance, Liu reported that the hemispherical apatite particles adhered to the PDA-coated PPBES surface, while pure PPBES group did not facilitate apatite formation. 25 On this basis, the NPEEK-PDA-(PLGA-NH 2 @pBMP-2) group had more positive ALP activity or calcium deposition. With the degradation of PLGA on the scaffold, it provided space for bone tissue repair and supported bone conduction, meanwhile pBMP-2 could persist in playing a role at the cell-implant interface, and the proliferated rBMSCs are continuously transfected to produce therapeutic BMP-2 protein.…”
Section: Discussionmentioning
confidence: 94%
“…This is mainly due to the strong chelation effect of PDA on calcium ions, which can enrich calcium ions on the surface of the material and induce the formation of hydroxyapatite crystals. For instance, Liu reported that the hemispherical apatite particles adhered to the PDA‐coated PPBES surface, while pure PPBES group did not facilitate apatite formation 25 . On this basis, the NPEEK‐PDA‐(PLGA‐NH 2 @pBMP‐2) group had more positive ALP activity or calcium deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Yao et al 46 investigated how modification of hydrophobic PCL substrates with the relatively hydrophilic PLA may enhance osteogenic differentiation of h‐MSCs. Furthermore, PD–known for improving material hydrophilicity 47 –was reported by Xu et al 48 and Deng et al 49 to enhance osteogenic differentiation of MSCs coupled with changes in substrate chemistry on HAp/polyamide 66 and electrospun PCL substrates, respectively. The reported enhancement in osteogenic differentiation due to alterations in scaffolds hydrophobicity may be a result of improved protein adsorption and cell adhesion to the scaffolds 50‐53 – both known to influence MSC osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%